2007
DOI: 10.1002/anie.200605165
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Bonding of CO on Cobalt Clusters by Coadsorption of H2

Abstract: Reactions of small molecules with transition metal nanoparticles have attracted considerable interest over the past decades since they can provide a conceptual framework for applications such as heterogeneous catalysis and hydrogen storage [1][2][3][4] . The reaction of H 2 and CO with Fe and Co nanoparticles has been widely studied due to the relevance to the Fischer-Tropsch process in which a mixture of H 2 and CO is converted into long chain hydrocarbons. An important step in this process is the breaking of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The frequency shifts as a function of cluster charge and size are consistent with the charge delocalization that is expected for a conducting sphere 71. The CO stretch can also act as a probe for co‐adsorbate induced changes in electronic structure of the cluster 72. These studies provide a direct link to surface science, where measurements of the CO stretch frequency have been used as a probe for the properties of surface sites 73.…”
Section: Stable Adsorbatessupporting
confidence: 68%
“…The frequency shifts as a function of cluster charge and size are consistent with the charge delocalization that is expected for a conducting sphere 71. The CO stretch can also act as a probe for co‐adsorbate induced changes in electronic structure of the cluster 72. These studies provide a direct link to surface science, where measurements of the CO stretch frequency have been used as a probe for the properties of surface sites 73.…”
Section: Stable Adsorbatessupporting
confidence: 68%
“…It has indeed been shown that the cluster charge is delocalized over the surface of the cluster. 57,58 However, a combination of a theoretical and more detailed spectroscopic study is needed to identify the reason for the absence of a D-D stretch absorption band for the nickel hydride complexes with more than 10 nickel atoms. 6.…”
Section: Resultsmentioning
confidence: 99%
“…Co-adsorption of hydrogen and carbon 14/27 monoxide onto 3d TM clusters has been investigated in more detail [80,81] inspired by the relevance of these systems in heterogeneous catalysis, e.g., for Fischer-Tropsch synthesis. Coadsorbed H can affect the interaction of CO with the cluster via site blocking leading to a stabilization of molecular CO on an early transition metal like vanadium [81], but it is also found to alter the C-O bond strength.…”
Section: Effects Of Electron Densitymentioning
confidence: 99%